EXISTENTIALISM PERSPECTIVE: CAN CHARACTER EDUCATION OVERCOME THE PHENOMENON OF BULLYING IN SCHOOLS? - Lastiadi Muhtadin (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
This article is a literature review on the perspective of existentialism philosophy in the application of character education to overcome bullying in schools. Education is a process, not just the development of aspects of knowledge or just the transfer of knowledge from person to person, but also the process of transforming values (transfer of values) and building character in all its aspects. One of the trends in the flow of education that is developing is existentialism. This school has a certain view of